2020
DOI: 10.1016/j.heliyon.2020.e03805
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground biomass allocation, additive biomass and carbon sequestration models for Pterocarpus erinaceus Poir. in Burkina Faso

Abstract: Efforts to develop allometric models for accurate estimation of biomass and carbon sequestration in Sub-Saharan African savanna ecosystems remain inconclusive. Most available allometric models are not site-specific, and hence do not account for the effects of regional climate variabilities on tree growth and capacity to sequester carbon. In contrast, site-specific biomass allometric models constitute a robust tool for forest and carbon emission management in the context of the reducing emissions from deforesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…What matters is therefore to use the additivity method in fitting models to allow an TAGB prediction with less bias as possible. Several methods exist in this area, but seemingly unrelated regression (SUR) is widely use in recent studies in Burkina Faso ( Dimobe et al., 2018 ; Ganamé et al., 2020 ), because it creates compatibility between the prediction of the tree's components biomass and TAGB ( Parresol et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…What matters is therefore to use the additivity method in fitting models to allow an TAGB prediction with less bias as possible. Several methods exist in this area, but seemingly unrelated regression (SUR) is widely use in recent studies in Burkina Faso ( Dimobe et al., 2018 ; Ganamé et al., 2020 ), because it creates compatibility between the prediction of the tree's components biomass and TAGB ( Parresol et al., 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this variable is always available in the inventory data. Numerous studies have also shown that DBH is the explanatory variable most commonly used for predicting the biomass of different compartments of woody species [10,11,36,69].…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of total height and wood density was therefore necessary to improve the quality of prediction of the biomass of leaves and branches of B. senegalensis in the zone studies. Some authors believe that the use of DBH alone as an explanatory variable would lead to an increase in the predicted biomass [21,36]. Previous studies have shown that incorporating height as a second variable improves the prediction performance of elaborate equations [10,26,36,70] and has the advantage of increasing the potential of applicability of the equations to different sites [71].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations